Negosiasi Praktik Keagamaan Lokal melalui al-‘Urf: Studi atas Praktik Tradisi Pelepasan Nazar di Danau Kalabborang Kabupaten Gowa - Fajri, Nurfaidah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
This study discusses the tradition of fulfilling vows carried out by the people of Pallantikang Village on Lake Kalabborang, Pattallassang District, Gowa Regency, from the perspective of al-'urf. The tradition of fulfilling vows is a form of religious practice that has grown and developed in Muslim communities as an expression of gratitude and fulfillment of promises to Allah SWT. However, in the context of modern society, the practice of local religious traditions is often viewed as problematic because it is feared to contain elements that contradict the teachings of monotheism. Therefore, an in-depth and objective study is needed to assess this tradition through a contextual Islamic law approach. The research method used is qualitative, combining normative (sharia) and sociological approaches. The data collection process was carried out through observation, interviews, and documentation. The research instruments consisted of the researcher as the main instrument, supported by writing and recording tools. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The purpose of this study is to identify and comprehensively examine the main issues contained in the tradition of releasing vows at Lake Kalabborang through the 'urf approach. The results of the study show that the tradition of releasing vows at Lake Kalabborang has high social and spiritual value for the local community. In addition to being a form of fulfilling a promise to Allah SWT, this tradition also serves as a means of strengthening social relations and preserving the cultural heritage of ancestors. Based on an analysis of the elements contained in this tradition, it was found that the practice of fulfilling vows at Lake Kalabborang does not contain elements of shirk or beliefs that contradict the principles of tawhid. Thus, this tradition can be categorized as 'urf shahih, which is a custom that is valid and acceptable according to Islamic law, reflecting a form of cultural locality that is in harmony with sharia values. The implications of this study emphasize the importance of preserving local traditions that are in harmony with Islamic teachings, as well as the need for religious and traditional leaders to play an active role in educating the community so that traditional practices remain within the corridor of monotheism. This study also contributes theoretically to the development of Islamic law studies based on local wisdom, particularly in the application of the concept of al-'urf.